Ion diffusion and acceleration in plasma turbulence. (December 2018) - Pecora, F.; Servidio, S.; Greco, A.; Matthaeus, W. H.; Burgess, D.; Haynes, C. T.; Carbone, V.; Veltri, P.
Abstract : Particle transport, acceleration and energization are phenomena of major importance for both space and laboratory plasmas. Despite years of study, an accurate theoretical description of these effects is still lacking. Validating models with self-consistent, kinetic simulations represents today a new challenge for the description of weakly collisional, turbulent plasmas. We perform simulations of steady state turbulence in the 2.5-dimensional approximation (three-dimensional fields that depend only on two-dimensional spatial directions). The chosen plasma parameters allow to span different systems, going from the solar corona to the solar wind, from the Earth's magnetosheath to confinement devices. To describe the ion diffusion we adapted the nonlinear guiding centre (NLGC) theory to the two-dimensional case. Finally, we investigated the local influence of coherent structures on particle energization and acceleration: current sheets play an important role if the ions' Larmor radii are of the order of the current sheet's size. This resonance-like process leads to the violation of the magnetic moment conservation, eventually enhancing the velocity-space diffusion.